MODEL PARTICIPATORY MULTIPLE INTELLIGENCES (PARMI) UNTUK PEMBELAJARAN MENULIS KARYA ILMIAH - Khabib Sholeh (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
Writing skills into a final charge of the most important master learners. Writing skills should be practiced and focused on higher education is to write scientific papers. In the meantime, until now there is no learning model appropriate to write scientific papers in order to improve the literacy skills of learners as may be necessary, especially in supporting their studies. Model of learning to write scientific papers should encourage learners to high literacy skills are supported by critical and creative thinking skills, and the ability to solve problems. The purpose of this study is (1) a description keterterapan level model of multiple intelligences oriented substantasi participation of students in the content and structure of the model design flexibility; and (2) description of the effectiveness model of multiple intelligences oriented learners participation resulting in an increase in learners' achievements in writing scientific papers. The criteria used as a basis to determine the validity of the instrument is to consider the value of lambda (λ) the provisions, if the lambda (λ)> 0.3 means the item number to be valid. The test is done in addition to the learning model is also equipped with a qualitative test quantitatively using equetion structural modeling (SEM) with Lisrel program. Effectiveness of the test design used was quasi experimental method (Quasi-Experimental design), the model Nonequivalent Control Group, carried out three times with t-test test. Analysis of the suitability test hypothetical models parmi model evaluation with field data based on the implementation of the test data, the results obtained following a) all seem to have the value of the variable load factor (λ)> 0.3; b) Chi-Square = 0.61, df = 1, ρ-value = 0.43 (> 0.05); c) RMSEA of 0.00 (<0.08); and d) GFI = 0.99 (> 0.90). The results of this analysis indicate the suitability parmi models with field data. In other words, the model is consistent with the data, so it can be used as a model of learning to write scientific papers in college. The average value of the critical-creative thinking skills in experiment 3 for the control group was 68.31, while the experimental group was 74.88. That is, treatment with parmi models affect the learning process. The results of the t test = 15,066> t table = 1.98. The difference in the average value was significant and proven to be effective in improving the ability of writing articles.